2022
DOI: 10.3390/rs14174275
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of Indoor Navigation Elements for Point Cloud of Buildings with Occlusions and Openings by Wall Segment Restoration from Indoor Context Labeling

Abstract: Indoor 3D reconstruction and navigation element extraction with point cloud data has become a research focus in recent years, which has important application in community refinement management, emergency rescue and evacuation, etc. Aiming at the problem that the complete wall surfaces cannot be obtained in the indoor space affected by the occluded objects and the existing methods of navigation element extraction are over-segmented or under-segmented, we propose a method to automatically reconstruct indoor navi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The level of detail is defined in five levels, from 0 to 5 (Figure 3) [27]. The reconstruction of the 3D model can be conducted simultaneously [2,9], or after labeling the interior spaces [15,18,23]. In some recent studies, the segmentation of spaces was discussed separately [4,24,25].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of detail is defined in five levels, from 0 to 5 (Figure 3) [27]. The reconstruction of the 3D model can be conducted simultaneously [2,9], or after labeling the interior spaces [15,18,23]. In some recent studies, the segmentation of spaces was discussed separately [4,24,25].…”
Section: Related Workmentioning
confidence: 99%
“…To conclude this section, gaps, noise and complexity of the point cloud, as well as the presence of interior furniture, should be considered as the main challenges of the building interior modeling process, which are still under discussion among researchers [23]. Our main goal in this study is to develop an innovative model-driven method to reduce the effect of the mentioned challenges in providing a solid, watertight 3D model of the interiors of multi-room environments.…”
Section: Related Workmentioning
confidence: 99%
“…A complete and dense point cloud is the fundamental condition for 3D computer vision applications such as point cloud classification, segmentation and other 3D analysis and evaluation methods [11][12][13][14][15]. In practical applications, a dense and complete point cloud helps to better reconstruct the 3D model of a physical object, which can be better applied to industry and production [16,17]. Therefore, it is of great theoretical significance and application value to study the recovery of dense and complete point clouds from the observed incomplete point cloud data.…”
Section: Introductionmentioning
confidence: 99%
“…Developing automatic 3D reconstruction methodologies for creating 3D models of indoor spaces, which can be used for architectural design for example [46].…”
mentioning
confidence: 99%